Obstetric, somatic and infectious risk factors for vulva sclerotic lichen - Lyudmila K. Osipova; Ekaterina V. Kolesnikova; Alexander V. Zharov; Milena A. Penzhoyan (RUDN Journal of Medicine, 2024)
Relevance. Until now, disputes among scientists about its etiology, pathogenesis, nomenclature and risk factors for the development of vulvar lichen sclerosis have not subsided, which actualizes the need for scientific research aimed at solving these problems. The aim of the study - to establish statistically significant clinical and anamnestic risk factors for vulvar lichen sclerosis. Materials and Methods. An electronic database was formed with data from 344 patients with lichen sclerosus of the vulva and 60 women without vulvar diseases aged 20-70 years on hereditary, obstetric-gynecological, somatic and infectious history. Astatistical comparative correlation analysis of the obtained data was carried out using the Spearman correlation coefficient (R0.15), nonparametric Mann - Whitney U test and Student t test (p0.05), Chi-square tests, Phi and Cramer statistics. Results and Discussion. Statistically significant (p0.05) risk factors for the development of vulvar lichen sclerosus (R, in descending order) were established: the presence of fibrocystic mastopathy (-0.29); late menarche (15 years and older) (-0.28); onset of menopause (-0.25); recurrent vulvo-vaginal infections (-0.18); recurrent bacterial vaginosis (-0.18); autoimmune thyroiditis(-0.16) and stage II obesity (-0.16). Also, the average number of abortions and births (1.23 and 1.49, respectively) in the group of patients with lichen sclerosis of the vulva is statistically significantly greater (p0.05) than the average value (0.27 and 1.13, respectively) in control group. Conclusion. The data obtained on the impact of obesity and autoimmune thyroiditis on the risk of developing vulvar sclerotic lichen are consistent with the results of global studies and confirm the association of the disease with autoimmune and metabolic disorders. Recurrent vulvo-vaginal infections and dysbiotic processes in the vagina can be both acause and aconsequence of vulvar lichen. The relationship between fibrocystic mastopathy and vulvar lichen sclerosus remains debatable and requires further research. Late menarche, the onset of menopause, alarge number of abortions and childbirth can also be considered triggers for vulvar lichen sclerosus in patients with agenetic predisposition to the disease.